1996
DOI: 10.1111/j.1600-9657.1996.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental injuries of permanent teeth treated in private practice in Athens

Abstract: Although there are several epidemiological studies on dental trauma internationally, there are not many studies that record, analyse and follow different kinds of dental trauma treated in a private office, and that evaluate how parameters such as type of dental trauma, as well as time lapse until treatment might influence the final outcome and the prognosis of the teeth. The sample consisted of 242 patients, 6-17 years of age, with 369 injured teeth treated within a period of 5 years. All the case were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
41
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 21 publications
17
41
2
1
Order By: Relevance
“…This is in contrast to other studies, where lateral tooth dislocations primarily involved the maxillary front region. 15,[18][19][20] Avulsions and dislocations are typically observed in the front teeth, where the direct impact generates forces that tend to displace the coronal portion orally, causing displacement of the root in the other direction or, ultimately, even avulsion of the tooth. 6 Falls were the most common cause of facial fractures in this study.…”
Section: Lieger Et Al Dental Injuries and Facial Fractures J Oral Mmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to other studies, where lateral tooth dislocations primarily involved the maxillary front region. 15,[18][19][20] Avulsions and dislocations are typically observed in the front teeth, where the direct impact generates forces that tend to displace the coronal portion orally, causing displacement of the root in the other direction or, ultimately, even avulsion of the tooth. 6 Falls were the most common cause of facial fractures in this study.…”
Section: Lieger Et Al Dental Injuries and Facial Fractures J Oral Mmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Avulsions were mostly observed in the maxilla, as found in other studies. [17][18][19][20][21][22] Lateral dislocations were found in the anterior segments of both jaws. This is in contrast to other studies, where lateral tooth dislocations primarily involved the maxillary front region.…”
Section: Lieger Et Al Dental Injuries and Facial Fractures J Oral Mmentioning
confidence: 99%
“…The highest occurrence of dental injury was found in the age interval of 9-10 years of age. 15,16,19,22,23 This could be attributed to the fact that children are usually more active in this period of life and often lack motoric coordination because of their developmental stage, 17 for this reason they cannot precisely evaluate velocity and danger. As they grow up, proneness to traumatic dental injuries is significantly reduced because of the decrease in predisposing factors indicated above.…”
Section: Methodsmentioning
confidence: 99%
“…24 According to the results of this study, the incidence of two injured teeth is more frequent in boys than in girls, which is similar to those of some recent studies. 11,15,18,[23][24][25][26][27] A possible cause of boys higher proneness to traumatic dental injuries could be their involvement in more aggressive sports, as well as their more violent behavior. 14-16,17.19,22,23 In general, high percentage of traumatic dental injuries to the maxillary teeth can be explained by the prominence of these teeth.…”
Section: Methodsmentioning
confidence: 99%
“…For example, there are many different specifications of dental and oral trauma reported in the literature. [7][8][9][10][11][12] Determining the incidence of a particular event requires information on the number of new cases in a specified time period divided by the number of persons exposed to the risk during this period. [7] The prevalence of orofacial trauma in various epidemiological studies has also been found to differ considerably.…”
Section: Discussionmentioning
confidence: 99%